Efektivitas Penggunaan ChatGPT dalam Pembelajaran Menulis Tingkat Lanjut Bahasa Prancis Mahasiswa UNIMED - Yenny Sarmi Manullang; Elvi Syahrin (Pusat riset dan Inovasi Nasional, 2025)
This study aims to explain the effectiveness of using ChatGPT version 3.5 on advanced writing production in Tendances A2, Unit 7, Learning 2, with the topic “Demander une autorisation” (Requesting Permission) for fourth-semester students of the French Language Education Program at Unimed. The issue addressed in this study is the lack of students' mastery of vocabulary and sentence structure, as well as the fact that ChatGPT has never been used as a learning medium in the advanced writing course. This issue is reflected in the students’ pre-test score, which was 32—still below the minimum passing score (KKM) of 75. The method employed in this research is an experimental method using a one-group pre-test and post-test design. The sampling technique used is purposive sampling. The study population consisted of all 17 students from Class B of the 2023 academic year. To analyze the effectiveness of the media used, several stages were carried out: pre-test, treatment, and post-test.